The concomitant lateral condyle and olecranon fracture in a six-year-old child: A case report - KC, Kapil Mani; GC, Raju; Acharya, Samir; Gnawali, Gopal Prasad (Journal of Karnali Academy of Health Sciences, 2022)
The concomitant lateral condyle and olecranon fractures in the same elbow occur very rarely. It is essential to do the needful clinical examination and appropriate anteroposterior and lateral radiographic views with a high index of suspension so as not to miss either of these fractures which otherwise lead to malunion, nonunion, tardy ulnar nerve palsy, and secondary osteoarthritis of elbow joint in adult age. We report a six-year-old male child with concomitant lateral condyle and olecranon fractures which were correctly diagnosed with a second standard radiograph and managed by open reduction and internal fixation with Kirschner wires with reasonable functional outcomes after surgical intervention.